2015
DOI: 10.1093/ofid/ofv193
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus Seroprevalence Among Children and Adolescents in Germany: Data From the German Health Interview and Examination Survey for Children and Adolescents (KiGGS), 2003–2006

Abstract: CMV seroprevalence increases with age and is significantly associated with migration background, country of origin, and place of birth. We identified the birth order of siblings, breastfeeding, early day care attendance and living in East Germany as further risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 37 publications
6
32
0
7
Order By: Relevance
“…This number is within the wide range of the previously published data for population groups in Europe of 30.4 to 89.7%. [9,11,[13][14][15][16][17][18][19]. The slight decrease of 0.77% from the previous decade (1998 to 2008) was not statistically significant (p = 0.0881).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…This number is within the wide range of the previously published data for population groups in Europe of 30.4 to 89.7%. [9,11,[13][14][15][16][17][18][19]. The slight decrease of 0.77% from the previous decade (1998 to 2008) was not statistically significant (p = 0.0881).…”
Section: Discussionmentioning
confidence: 84%
“…In our youngest patients, below the age of 20 years, and in the age group 30-39 years, however, the trend halted or even reversed. In the youngest patients, this might be associated with more children below the age of 3 years attending daycare, where the exposure to potentially infectious toddlers as a source of infection is increased, a known factor associated with CMV seropositivity in Germany [15]. Notably, from 2006 to 2017, the percentage of children below the age of 3 years attending day care in Germany increased from 13.6 to 33.1% [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Voigt et al determined that the seroprevalence of CMV was 27.4% in population of children and adolescents in Germany. They also reported that CMV seropositivity was significantly associated with low socioeconomic status and migration background (such as country of origin and place of birth) [13]. The rate of CMV seroprevalence among pregnant woman in Turkey was reported in the range of 92.6%-98.7% [14].…”
Section: Resultsmentioning
confidence: 99%
“…Incidence and prevalence of CMV infection are associated with poor socio-economic status (SES), between countries as well as within countries and communities 49, 64, 65, 100, 114116 . This includes association with crowding, in particular the number of young children in household 117119 .…”
Section: Epidemiological Convergencementioning
confidence: 99%